Rethinking family practices - Morgan, D. H. J. (Basingstoke ; New York : Palgrave Macmillan, 2011)
"Leading family sociologist David Morgan revisits his highly influential 'family practices' approach in this new book. Exploring its impact, and how it has been critiqued, Morgan shows the continued relevance of the approach with reference to time and space, the body, emotions, ethics and work/life balance"--
Machine generated contents note: -- The Original Argument -- Locating Practices -- Locating Practices: Alternatives -- Developments and Difficulties -- Time, Space and Family Practices -- The Body and Family Practices -- Emotions and Family Practices -- The Ethical Turn in Family Studies -- Work/Family Articulation -- Conclusion.
Includes bibliographical references and index.
Keywords: Families